Improving PISA Reading Literacy: The Effectiveness of KWL Strategy for Middle School Students' Comprehension of Descriptive Texts - Mercy Emmanuel; Torebaeva Firuza; Jaup Zenuni; Aladji Mamadou Sane (Journal of Language, Literature, and Educational Research, 2025)
Purpose of the study: This classroom action research aimed to investigate whether the Know-Want-Learned (KWL) strategy could improve the reading comprehension of descriptive texts among seventh-grade junior high school students, with implications for addressing the foundational literacy skills measured by international assessments such as PISA (Programme for International Student Assessment). Methodology: Employing the Kemmis & McTaggart model over two cycles, this study collected data using pre-tests, post-tests, observation sheets, teacher interviews, and student questionnaires. Quantitative data from tests were analyzed by calculating mean scores and the percentage of students passing the Minimum Mastery Criterion (KKM), while qualitative data were analyzed thematically to assess engagement and metacognitive development. Main Findings: The implementation of the KWL strategy significantly improved student outcomes. The percentage of students passing the KKM increased from 20% in the pre-test to 40% in post-test 1, and further to 80% in post-test 2. Qualitative data indicated increased student enthusiasm, active participation, and the development of metacognitive strategies such as questioning and reflection that align with core PISA reading literacy competencies. Novelty/Originality of this study: This study provides empirical evidence from an Indonesian junior high school context, specifically linking the KWL strategy not only to improved classroom performance but also to the development of higher-order reading skills relevant to PISA frameworks. It demonstrates KWL as a practical, low-tech strategy that can help bridge the gap between daily instruction and the literacy competencies emphasized in global assessments.